2009
DOI: 10.2114/jpa2.28.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meal Habits and Alcohol/Cigarette Consumption on Morningness-Eveningness Preference and Sleep Habits by Japanese Female Students Aged 18–29

Abstract: The relationship of meal habits and alcohol/ cigarette consumption to circadian typology and sleep health in Japanese female students was studied from an epidemiological point of view. Questionnaires on Morningness-Eveningness by Torsvall and Åkerstedt (1980), sleep habits, regularity of meal intake and meal amount, and style of alcohol and cigarette consumption were administered to 800 students aged 18-29 years, attending university or training schools for nutrition specialists (Aichi Prefecture, 35°N). Point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 26 publications
4
64
0
2
Order By: Relevance
“…Despite academics being the frequent reason given for energy drink consumption, evening types or daytime sleepers do not exhibit higher academic performance compared to their counterparts 12, 29, 36, 41, 42 . Additionally, there is a large body of evidence that shows daytime sleepers and evening types are strongly associated with numerous health and social problems 7–9, 11, 13, 46 . From a public health promotion and disease prevention standpoint, these findings suggest an obvious need for effective educational and prevention programs targeted toward improving sleep hygiene and reducing consumption of energy drinks among young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Despite academics being the frequent reason given for energy drink consumption, evening types or daytime sleepers do not exhibit higher academic performance compared to their counterparts 12, 29, 36, 41, 42 . Additionally, there is a large body of evidence that shows daytime sleepers and evening types are strongly associated with numerous health and social problems 7–9, 11, 13, 46 . From a public health promotion and disease prevention standpoint, these findings suggest an obvious need for effective educational and prevention programs targeted toward improving sleep hygiene and reducing consumption of energy drinks among young adults.…”
Section: Discussionmentioning
confidence: 99%
“…4 Hourly distribution of energy intake per 24 h during the breakfast ( ) and no-breakfast ( ) conditions for male participants who typically eat breakfast at least 5 times/week typically observed in experimental situations compared with free-living surveys (36) , this psychological difference between male and female participants could account for the different responses between the female highfrequency breakfast eaters and the male participants. Differences between the female high-and low-frequency breakfast eaters may be linked to differences in routinedriven eating habits and/or to dietary restraint between regular and irregular breakfast eaters (27,41) .…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires (IPAQ, SF-36v2 and morningness) were scored according to published guidelines (27)(28)(29) . Data on physical activity and health status dimensions were not normally distributed, as is typical for data of this type (31) .…”
Section: Statistical Analysesmentioning
confidence: 99%
“…These results mean that dinner at a later time was related to delayed bedtime in the LF group, and eating breakfast was associated with an earlier bedtime in the LA group. Many studies have suggested a relationship between meal habits and sleep pattern and/or sleep quality (e.g., Arakawa et al 2001;Tanaka et al 2002;Nakade et al 2009). Moreover, studies on mammals such as rodents suggest that the timing of food intake may entrain the internal biological clock system either directly or indirectly through other neural or peripheral systems (Mendoza 2007).…”
Section: Discussionmentioning
confidence: 99%